Patterns of Geographic Expansion of Aedes aegypti in the Peruvian Amazon - Guagliardo, Sarah Anne (Public Library of Science, 2014)
BACKGROUND AND OBJECTIVES: In the Peruvian Amazon, the dengue vector Aedes aegypti is abundant in large urban centers such as Iquitos. In recent years, it has also been found in a number of neighboring rural communities with similar climatic and socioeconomic conditions. To better understand Ae. aegypti spread, we compared characteristics of communities, houses, and containers in infested and uninfested communities. METHODS: We conducted pupal-demographic surveys and deployed ovitraps in 34 communities surrounding the city of Iquitos. Communities surveyed were located along two transects: the Amazon River and a 95km highway. We calculated entomological indices, mapped Ae. aegypti presence, and developed univariable and multivariable logistic regression models to predict Ae. aegypti presence at the community, household, or container level. RESULTS: Large communities closer to Iquitos were more likely to be infested with Ae. aegypti. Within infested communities, houses with Ae. aegypti had more passively-filled containers and were more often infested with other mosquito genera than houses without Ae. aegypti. For containers, large water tanks/drums and containers with solar exposure were more likely to be infested with Ae. aegypti. Maps of Ae. aegypti presence revealed a linear pattern of infestation along the highway, and a scattered pattern along the Amazon River. We also identified the geographical limit of Ae. aegypti expansion along the highway at 19.3 km south of Iquitos. CONCLUSION: In the Peruvian Amazon, Ae. aegypti geographic spread is driven by human transportation networks along rivers and highways. Our results suggest that urban development and oviposition site availability drive Ae. aegypti colonization along roads. Along rivers, boat traffic is likely to drive long-distance dispersal via unintentional transport of mosquitoes on boats.